Speed of sound constraints on maximally-rotating neutron stars - Margaritis, Chrysovalantis; Koliogiannis Koutmiridis, Polychronis; Moustakidis, Charalampos (HNPS Advances in Nuclear Physics, 2020)
In the present work we provide a theoretical treatment concerning the effects of the upper bound of the sound speed in dense matter on the bulk properties of maximally-rotating (at mass-shedding limit) neutron stars. We investigate to what extent the possible predicted (from various theories and conjectures) upper bounds on the speed of sound constrain various key quantities, such as the maximum mass and the corresponding radius, Keplerian frequency, Kerr parameter and moment of inertia. We mainly focus on the lower proposed limit, , and we explore in which mass region a rotating neutron star collapses to a black hole. In any case, useful relations of the mentioned bulk properties with the transition density are derived and compared with the corresponding non-rotating cases.